PPM LENTO MBOK GEDE PADA BUMDES SUN GEDE MAKMUR DI DESA SUMBERGEDE KECAMATAN WRINGINANOM KABUPATEN GRESIK - Andri Krisnadianto; Dwiyana Anella Kurniasari; Yurifar Burhanudin; Meylinda Thirta Arlina (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Sun Gede Makmur is a Village Owned Enterprise (BUMDes) in Sumbergede Village, Wringinanom District, Gresik Regency. BUMDes Sun Gede Makmur has a traditional food product, namely Lento with the product name Lento Mbok Gede. The problems faced by partners are (1) not having an online marketing strategy. (2) packaging (Packaging) is less attractive so that sales of Lento Mbok Gede products are less. (3) The production process so far does not yet have a production standard. So Lento Mbok Gede community service at Bumdes Sun Gede Makmur in Sumbergede Village, Wringinanom District, Gresik Regency. Based on this, the method used is Training and Mentoring to provide solutions to partner problems, namely (1) Training and Assistance in creating online shop accounts. (2) new packaging (Upgrade Packaging) which is more attractive for Lento Mbok Gede products. (3) Formulating and producing a Standard Operating Procedure Book (SOP) for the Lento Mbok Gede Production Process to increase production yields that have the same quality. The results of this community service, (1) Sun Gede Makmur already has an online shop account with the name LentoMbok. (2) Lento Mbok Gede has a new packaging with a more attractive appearance, (3) Sun Gede Makmur has a SOP for the Lento Mbok Gede Production Process.